2014
DOI: 10.1002/wat2.1016
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the dynamics of black carbon and associated contaminants in glacial systems

Abstract: More than one billion people depend upon glaciers for water, yet this exploitation is seldom underpinned by science-led water management practice. Previous work has detected that glaciers store and then subsequently release contaminants to downstream ecosystems, revealing a potentially harmful legacy that needs to be managed in conjunction with contemporary atmospheric pollution and climate change. Remarkably, while several classes of harmful organic pollutants have been considered in this context, almost no a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Furthermore, snow grain packing also plays a critical role in affecting the albedo of both clean and dirty snow . High SDI and I imp values are found across the ELA (equilibrium line altitude; located approximately at 3000 m, following Zekollari et al, 2014), where Saharan dust layers probably associated with heavy depositions that occurred during the hydrologic year 2014(Di Mauro et al, 2015Varga et al, 2014) appear on the glacier surface. The presence of outcropping dust across and above the ELA of an Alpine glacier during the summer season further decreases its reflectance and enhances the melt at higher altitude, where new snow and firn are directly exposed to solar radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, snow grain packing also plays a critical role in affecting the albedo of both clean and dirty snow . High SDI and I imp values are found across the ELA (equilibrium line altitude; located approximately at 3000 m, following Zekollari et al, 2014), where Saharan dust layers probably associated with heavy depositions that occurred during the hydrologic year 2014(Di Mauro et al, 2015Varga et al, 2014) appear on the glacier surface. The presence of outcropping dust across and above the ELA of an Alpine glacier during the summer season further decreases its reflectance and enhances the melt at higher altitude, where new snow and firn are directly exposed to solar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The Alps rise on the top of the Po river plain, one of the most industrialized and densely populated areas of Europe. As a consequence, the presence of anthropogenic activities is expected to strongly influence the geochemical and radiative characteristics of cryoconite (Baccolo et al, 2017;Cook et al, 2015;Hodson, 2014;Tieber et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cryoconite in holes has higher concentration of organic matter and inorganic nutrients (nitrogen, phosphorus...) than the surrounding ice and supraglacial sediments [35,36]. This characteristic leads, on the one hand, to the incorporation of hydrophobic compounds such as POPs into the cryoconite organic matter [6] and, on the other hand, it promotes the presence of biodiverse and active microbial communities [37], which can biodegrade the contaminants.…”
Section: Accumulation Of Pollutants and Microbiological Response In Cmentioning
confidence: 99%
“…The organic contaminants in these remote areas are referred to as persistent organic pollutants (POPs), which consist of several groups of chemicals with similar structures and physical-chemical properties that are extensively used worldwide in agriculture (pesticides), industrial and health applications. Recent studies have revealed that alpine environments are affected by the presence of POPs [4][5][6]. These chemicals are ubiquitous, show long-range transport potential, and many of them are hydrophobic.…”
Section: Introductionmentioning
confidence: 99%
“…Glaciers on the Tibetan Plateau are currently an important sink in the global Hg cycle, but with a warming climate they may become a Hg source that could endanger ecosystems and human health in the region (Huang et al, 2012). Glacier dynamic models project future increases in contaminant releases from glacier melt (Hodson, 2014).…”
Section: Introductionmentioning
confidence: 99%